The Role of Servant Leadership Components on the Organizational Effectiveness in Zabol University - Mohammad Ghasemi (Journal of Global Pharma Technology, 2018)
Servant leadership with the impact on the Organizational effectiveness is one of the factors that affect the efficiency and effectiveness, which are considered the most important goals of an organization and it should be taken a step to be strengthened. So, the aim of this research is explaining the impact of servant leadership components on the Organizational effectiveness of staffs of Zabol University. Since the purpose of this research is explaining the impact of the servant leadership components on the Organizational effectiveness of staffs. In terms of goal is applied research, based on the descriptive nature, that is kind of correlation and in terms of procedure is quantitative. The statistical population of this research consists of all staffs of the Zabol University, which are 305 individuals. To determine the sample size by using the method of Morgan table, 169 individuals have chosen and the method of sampling for this study is simple random. In this research, in order to collect theoretical basics and background, it has been used the library studies and articles and academic journals. As well as collecting statistical data in order to test the hypothesis of the research, it has been used field method and questionnaire, that their validity and reliability have been approved. In this study, after gathering the questionnaires, the data file will be formed in SPSS software and according to the number of variables and the type of study as well as the relationships between variables were by using the tables of frequency, diversity indices of bar graphs, the histogram used both descriptive and inferential statistics. In the level of inferential statistics has been used linear regression test and step by step to show the impact of the servant leadership and its components on the Organizational effectiveness of the staffs. The findings of the research showed that the servant leadership and its components of the productivity of staffs of Medical Science University have a significant impact.Keywords: servant leadership, productivity, staffs, Medical Science University